A Modular Approach Towards Fluorescent pH and Ascorbic Acid Probes Based on Ring‐Opening Metathesis Polymerization. Issue 1 (22nd October 2013) - Gallas, Katharina; Knall, Astrid‐Caroline; Scheicher, Sylvia R.; Fast, David E.; Saf, Robert; Slugovc, Christian
<x xml:space="preserve">Abstract</x> Copolymerization represents a modular synthetic strategy toward optochemical sensors by disassembling small molecule probes and recombining them to screen various fluorophore‐quencher combinations, instead of synthesizing individual sensor molecules. To demonstrate this, a polymerizable, fluorescent 1, 6, 7, 12‐tetrachloroperylene‐3, 4:9, 10‐bis(dicarboximide) derivative with a norbornene ester side chain is prepared and copolymerized with a tertiary‐amine‐bearing monomer, as well as an oligo‐glycol‐bearing monomer, via ring‐opening metathesis polymerization (ROMP). In this manner, water‐soluble optical pH sensor polymers (with apparent pka values of 6.4–7) are obtained. The effect of the macromolecular architecture on the sensing performance is evaluated, whereby a diblock copolymer structure made of an oligoglycol segment and a segment containing the secondary amine and the fluorescent moiety is identified as being most favorable for pH sensing. Similarly, profluorescent polymers are obtained by employing nitroxides instead of secondary amines, which allows detection of ascorbic acid (with a detection limit of 0.1 × 10−3m) in water. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>